Relevance of Pragmatism Philosophy in the Development of Indonesian Language Curriculum with Tyler Model - Mariam Ulfa; Ria Kristia Fatmasari; Rozekki; M.Helmi; Junal (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The Indonesian educational landscape is transitioning from the philosophical advocacy of the Merdeka Belajar (Independent Learning) policy to the practical implementation of Deep Learning pedagogies. This transition is critical for the Indonesian Language subject, which is central to fostering critical discourse and national identity. This conceptual research article argues that the philosophy of Pragmatism provides a robust foundation for Deep Learning, while the Tyler Model offers a systematic framework for its implementation. Employing a critical qualitative literature review, this study deconstructs the current implementation challenges in Indonesia. The findings reveal a gap between policy ideals and classroom practice, where projects often remain superficial. The synthesis demonstrates how each stage of the Tyler Model—from formulating competency-based objectives to designing authentic learning experiences and performance assessments—can be guided by Pragmatist principles to create a coherent Deep Learning environment. The study concludes that a deliberate integration of these frameworks is essential for moving beyond ceremonial compliance towards a transformative Indonesian language curriculum that empowers students as critical thinkers, collaborative problem-solvers, and effective communicators.